PENINGKATAN KESADARAN MASYARAKAT TERHADAP DAMPAK KEKERASAN DALAM RUMAH TANGGA (KDRT) BAGI KESEHATAN MENTAL ANAK - Yuswita, Yuswita; Liananiar, Liananiar; Nuraina, Nuaraina; Hanum, Zulfa; Saskia, Putri Wildatul; Ernida, Yulia (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity examined the impact of domestic violence on children's mental health. The background includes an increase in the incidence of domestic violence and it is important for families to understand the impact on children's mental health. Domestic violence is an action committed by a person or several individuals against another person. These actions result in physical, sexual and psychological pain, risk of exclusion, coercion, and even death in the household. This community service activity aimed to identify the effects of domestic violence on children's mental health. The method of implementing activities was through seminars and discussions held in Blang Asan Village and attended by the local community. The results of implementing this PKM activity showed that domestic violence can cause trauma, fear and insecurity, lack of self-confidence, behavioral problems, difficulty forming relationships, and can imitate violent behavior. Therefore, love in the form of protection and attention must be given to children affected by domestic violence to support children's mental health.